2020
DOI: 10.1016/j.molcel.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ectosomal PKM2 Promotes HCC by Inducing Macrophage Differentiation and Remodeling the Tumor Microenvironment

Abstract: Highlights d HCC-cell-derived ectosomal PKM2 induces monocyte-tomacrophage differentiation d Remodeling tumor microenvironment by ectosomal PKM2 promotes HCC progression d Sumoylation facilitates PKM2 sorting into ectosomes in an ARRDC1-dependent manner d Macrophage-secreted CCL1 reinforces PKM2 ectosomal excretion in a feedforward loop

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 54 publications
6
139
0
1
Order By: Relevance
“…Peptide SMIM30 promotes HCC development by inducing SRC/YES1 membrane anchoring and MAPK pathway activation [17]. Ectosomal PKM2 promotes HCC by inducing macrophage differentiation and remodeling the tumor microenvironment [18]. And the prognostic model composed of multiple genes can better predict the OS in HCC patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Peptide SMIM30 promotes HCC development by inducing SRC/YES1 membrane anchoring and MAPK pathway activation [17]. Ectosomal PKM2 promotes HCC by inducing macrophage differentiation and remodeling the tumor microenvironment [18]. And the prognostic model composed of multiple genes can better predict the OS in HCC patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…This is mediated by ARRDC1 and ARRDC4, which independently stimulate ARMM formation [Mackenzie et al., 2016]. Interestingly, selective targeting to ARMMs may not be limited to membrane proteins because hepatocellular carcinoma‐derived ectosomes contain the pyruvate kinase M2 (PKM2) isoform, an enzyme which catalyses the final step of glycolysis and is highly expressed in cancer cells [Hou et al., 2020]. The sorting mechanism of this soluble enzyme to ARMMs is not yet deciphered, but it depends on prior sumoylation as well as on ARRDC1, with whom PKM2 interacts.…”
Section: New Functions Of Arrdcs In Intercellular Communication Throumentioning
confidence: 99%
“…On the other hand, some proteins in TEXs can partially reflect the dysregulated protein profile in tumor cells, reveal the characteristics of tumor cells, and provide a new direction for the diagnosis or prognostic evaluation of tumors 12,13 . Numerous recent studies have confirmed that exosomes play a vital role in the progression of HCC [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 96%